Retrofit de edificações: estudo de reabilitação e adaptação das edificações antigas às necessidades atuais - Barrientos, Maria Izabel Garrido Garcia (2004)
Almost all old buildings had been constructed with concepts that nowadays are not more functional. Those constructions need a retrofit, that it is a rnanaged reform of the building, adapting the constructions to the new necessities, through the search for the optimization of the perforrn activities. This research evaluates cities evolutionary process, and the current valuation of downtown forgotten for years. The agents of the retrofit process, its characteristics and advantages will be discussed, such as: the degradation for the use, the user's profile changes, the end of materials useful life, the concern with the energy efficiency, and the technological innovations, propitiated by automation. It's also, presented a proposal methodology of diagnosis and available computational tools in the market.